2016
DOI: 10.1111/jfs.12304
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation and antibiotic resistance pattern of dominant Staphylococcus aureus clonal lineages in China

Abstract: Biofilm formation usually increases antimicrobial resistance capacity of Staphylococcus aureus, which poses considerable challenges to successful eradication of staphylococcal infections. Very little is known about the biofilm-forming capacity and antibiotic resistance pattern of dominant S. aureus clonal lineages in China. In this study, the disk diffusion method and the microtiter plate assay were, respectively, performed to determine the antibiotic resistance and biofilm-forming capacity of 84 different S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
1
14
1
1
Order By: Relevance
“…aureus (Tang et al, 2012;Lee et al, 2014). Biofilm formation can lead to persistent contamination or infection because the cells within the biofilm are very resistant to sanitation procedures and to the action of the host immune system and antimicrobial agents (Song et al, 2016). Different sources of Staph.…”
Section: Introductionmentioning
confidence: 99%
“…aureus (Tang et al, 2012;Lee et al, 2014). Biofilm formation can lead to persistent contamination or infection because the cells within the biofilm are very resistant to sanitation procedures and to the action of the host immune system and antimicrobial agents (Song et al, 2016). Different sources of Staph.…”
Section: Introductionmentioning
confidence: 99%
“…Sultan Zainal Abidin, Kuala Nerus, Terengganu, Malaysia. Direct inquiries to authors Puah and Chua (E-mail: suatmoi@um.edu.my & khchua@um.edu.my). it to cause infections (Foster, Geoghegan, Ganesh, & Hook, 2014). Moreover, S. aureus is a highly adaptable bacterium which has the ability to form structures known as biofilms among clinical and environmental strains (Song et al, 2017;Taj, Essa, Aziz, & Kazmi, 2012). According to Costerton, Stewart, and Greenberg (1999), biofilm is a structured community of bacterial cells enclosed in a self-produced polymeric matrix and adherent to an inert or living surface.…”
Section: Introductionmentioning
confidence: 99%
“…The isolates also harboured intercellular adhesion proteins (icaA, icaB, icaC, icaD, icaR) associated with attachment, proliferation and differentiation of micro-colonies into unique biofilm structures protecting them from the host defences such as antibodies or phagocytosis, making them extremely difficult to eradicate [54,55]. The association of dominant clonal lineages and biofilm formation has been reported in various studies on MRSA [56][57][58][59]. Naicker et al reported a strong biofilm formation in ST612 compared to the other clones which may have contributed to its dominance in South Africa [60].…”
Section: Discussionmentioning
confidence: 94%